(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. Aminoglycosides nephrotoxicity limits their use in clinical practice. Growth hormone-releasing peptide-6 (GHRP6) and epidermal growth factor (EGF) have proven cytoprotective effects in various tissues, including the kidney. This study aimed to determine the cytoprotective effect of EGF and GHRP6 on glomerular, proximal tubular, and interstitial morphology in rats treated with an overdose of kanamycin. Materials and Methods. Forty-four male Wistar adults rats were submitted to treatment for 20 days with sodium phosphate saline buffer (control group), kanamycin (kanamycin group), kanamycin and EGF (EGF group), kanamycin and GHRP6 (GHRP6 group), kanamycin, EGF, and GHRP6 (EGF-GHRP6 group). The kidneys were studied both during acute kidney injury (n = 19) and recovery phases (n = 25). The percentages of glomerular damage, tubular damage (reversible and irreversible changes), and interstitial damage were quantified in 10 histological fields per kidney using paraffin-embedded sections. Results. The damage in the glomeruli, proximal tubules, and interstitium was less in the groups treated with the cytoprotective treatments than in kanamycin group during acute kidney injury. During the recovery phase, normal structure of several glomeruli and the interstitium was appreciated in the EGF and GHRP6 groups, although tissue repair was not as complete as it in the EGF-GHRP6 group. In the recovery phase, cytoprotective treatments accelerated the recovery of tubular damage and reversible tubular changes prevailed. Conclusions. These results confirm the cytoprotective properties of EGF and GHRP6 alone and in combination and suggest the possibility of using these agents to accelerate kidney tissue repair after aminoglycoside-induced renal damage.